2019
DOI: 10.1038/s41419-019-1949-7
|View full text |Cite
|
Sign up to set email alerts
|

SPRY4 is responsible for pathogenesis of adolescent idiopathic scoliosis by contributing to osteogenic differentiation and melatonin response of bone marrow-derived mesenchymal stem cells

Abstract: Adolescent idiopathic scoliosis (AIS) is a complex, three-dimensional deformity of the spine that commonly occurs in pubescent girls. Decreased osteogenic differentiation and aberrant melatonin signalling have been demonstrated in mesenchymal stem cells (MSCs) from AIS patients and are implicated in the pathogenesis of AIS. However, the molecular mechanisms underlying these abnormal cellular features remain largely unknown. Our previous work comparing gene expression profiles between MSCs from AIS patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…55,58,59 Under normal conditions, melatonin via an MT2 response has effects on bone metabolism that can result in increases in bone density and bone mass. Melatonin promotes the proliferation of osteoblasts and differentiation of mesenchymal stem cells into osteoblasts via MT2 receptors 4,[60][61][62] and the MAPK pathway. 4 And Wang W et al denoting the presence of a functional abnormality of the melatonin signaling pathway (MT2) in the growth plate chondrocytes in AIS, which might be associated with the abnormal endochondral ossification in AIS patients.…”
Section: The Mechanism Of Action Of Melatonin In Aismentioning
confidence: 99%
See 1 more Smart Citation
“…55,58,59 Under normal conditions, melatonin via an MT2 response has effects on bone metabolism that can result in increases in bone density and bone mass. Melatonin promotes the proliferation of osteoblasts and differentiation of mesenchymal stem cells into osteoblasts via MT2 receptors 4,[60][61][62] and the MAPK pathway. 4 And Wang W et al denoting the presence of a functional abnormality of the melatonin signaling pathway (MT2) in the growth plate chondrocytes in AIS, which might be associated with the abnormal endochondral ossification in AIS patients.…”
Section: The Mechanism Of Action Of Melatonin In Aismentioning
confidence: 99%
“…Melatonin promotes the proliferation of osteoblasts and differentiation of mesenchymal stem cells into osteoblasts via MT2 receptors 4,[60][61][62] and the MAPK pathway. 4 And Wang W et al denoting the presence of a functional abnormality of the melatonin signaling pathway (MT2) in the growth plate chondrocytes in AIS, which might be associated with the abnormal endochondral ossification in AIS patients. 63 There is evidence of abnormal signaling of the downstream melatonin MT2/PKC pathway that may be related to reduced osteogenic differentiation and bone tissue mineralization.…”
Section: The Mechanism Of Action Of Melatonin In Aismentioning
confidence: 99%
“…Studies have revealed that melatonin can boost osteoblast differentiation by upregulating osterix protein stability and expression (14), reduce autophagy in high glucose-cultured osteoblasts, and alleviate diabetes-induced osteoporosis by suppressing the ERK pathway (29). In addition, melatonin restores the osteoporosis-impaired osteogenic potential of bone marrow-derived MSCs by preserving SIRT1-mediated intracellular antioxidation(30), and SPRY4 may be partially responsible for the melatonin-mediated osteogenesis of bone marrow-derived MSCs (31). However, it is generally unknown how melatonin promotes the osteogenic potential of bone marrow-derived MSCs undergoing aging.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3 secretion was significantly higher in DISH-BMSCs than NC-BMSC BMSCs have been reported to secrete a variety of cytokines to regulate osteogenic differentiation. (11)(12)(13) To determine the potential factors involved in the enhanced osteogenic differentiation of DISH-BMSCs, we analyzed cytokine expression in culture supernatants using a human cytokine array kit (Supplemental Fig. S4A).…”
Section: Dish-bmscs Exhibited Stronger Osteogenic Differentiation Abi...mentioning
confidence: 99%
“…(9,10) Moreover, BMSCs also regulate osteogenic differentiation by secreting autocrine and paracrine cytokines. (11)(12)(13) Abnormal osteogenic differentiation of BMSCs has been noted as a key mechanism for ectopic ossification in ankylosing spondylitis (AS). (12)(13)(14) Xie and colleagues (12) reported that an imbalance between BMP-2 and Noggin secretion by BMSCs could induce abnormal osteogenic differentiation and accelerated the progression of hyperostosis in AS.…”
Section: Introductionmentioning
confidence: 99%